Biochemical and physiological insights into TRH receptor-mediated signaling - Trubacova, Radka; Drastichova, Zdenka; Novotny, Jiri (Frontiers in Cell and Developmental Biology, 2022)
Thyrotropin-releasing hormone (TRH) is an important endocrine agent that regulates the function of cells in the anterior pituitary and the central and peripheral nervous systems. By controlling the synthesis and release of thyroid hormones, TRH affects many physiological functions, including energy homeostasis. This hormone exerts its effects through G protein-coupled TRH receptors, which signal primarily through Gq/11 but may also utilize other G protein classes under certain conditions. Because of the potential therapeutic benefit, considerable attention has been devoted to the synthesis of new TRH analogs that may have some advantageous properties compared with TRH. In this context, it may be interesting to consider the phenomenon of biased agonism and signaling at the TRH receptor. This possibility is supported by some recent findings. Although knowledge about the mechanisms of TRH receptor-mediated signaling has increased steadily over the past decades, there are still many unanswered questions, particularly about the molecular details of post-receptor signaling. In this review, we summarize what has been learned to date about TRH receptor-mediated signaling, including some previously undiscussed information, and point to future directions in TRH research that may offer new insights into the molecular mechanisms of TRH receptor-triggered actions and possible ways to modulate TRH receptor-mediated signaling,